Octarepeat region flexibility impacts prion function, endoproteolysis and disease manifestation - Agnes Lau; Alex McDonald; Nathalie Daude; Charles E Mays; Eric D Walter; Robin Aglietti; Robert CC Mercer; Serene Wohlgemuth; Jacques van der Merwe; Jing Yang; Hristina Gapeshina; Chae Kim; et al. (EMBO Molecular Medicine)
Abstract The cellular prion protein (PrPC) comprises a natively unstructured N‐terminal domain, including a metal‐binding octarepeat region (OR) and a linker, followed by a C‐terminal domain that misfolds to form PrPSc in Creutzfeldt‐Jakob disease. PrPC β‐endoproteolysis to the C2 fragment allows PrPSc formation, while α‐endoproteolysis blocks production. To examine the OR, we used structure‐directed design to make novel alleles, ‘S1’ and ‘S3’, locking this region in extended or compact conformations, respectively. S1 and S3 PrP resembled WT PrP in supporting peripheral nerve myelination. Prion‐infected S1 and S3 transgenic mice both accumulated similar low levels of PrPSc and infectious prion particles, but differed in their clinical presentation. Unexpectedly, S3 PrP overproduced C2 fragment in the brain by a mechanism distinct from metal‐catalysed hydrolysis reported previously. OR flexibility is concluded to impact diverse biological endpoints; it is a salient variable in infectious disease paradigms and modulates how the levels of PrPSc and infectivity can either uncouple or engage to drive the onset of clinical disease.